Hyaluronic Acid Soft Tissue Filler for the Treatment of The Hypoplastic Chin: An Observational Study. Issue 8 (August 2020) - Beer, Kenneth; Stonehouse, Anthony; Dunn, Monica
Abstract : BACKGROUND: The hypoplastic chin is associated with facial unattractiveness. OBJECTIVE: To evaluate safety and efficacy of JUVÉDERM Voluma XC Injectable Gel (hyaluronic acid filler, HAF) for treatment of hypoplastic chin. METHODS: This was a one-year, open-label, single-center study. RESULTS: Thirty subjects received HAF injections of which 24 subjects (80%) completed the study. Mean facial angle significantly improved at all time points compared with baseline, improving by 1.83° (95% confidence interval, 0.91, 2.75; p < .001) at 12 months. Subject satisfaction with lower face and jawline increased significantly for all FACE-Q questions and time points compared with baseline ( p < .05). Subject satisfaction with overall facial appearance, and percentage of subjects "not bothered" by area under chin increased significantly for most FACE-Q questions and time points compared with baseline ( p < .05). CONCLUSION: In this completed one-year study, HAF injection for hypoplastic chin was safe and accompanied by significant improvement in facial angle, measures of subject satisfaction, and GAIS. Abstract : Supplemental Digital Content is Available in the Text.